Stockpile scheduling with geometry constraints in dry bulk terminals. (June 2021) - Burdett, Robert L.; Corry, Paul; Eustace, Colin
Highlights: A new scheduling approach is proposed for dry bulk terminals. More realistic solutions are created as stockpile geometry constraints are included. Stockpiles are modelled using bench block models. Each bench block model is a collection of heterogeneous blocks. This article permits different reclaiming and stacking approaches to be evaluated. Abstract: In this article we consider how to construct schedules for the stacking and reclaiming activities of high-throughput dry-bulk export terminals (DBET) that operate large machines called stacker-reclaimers (SR) and handle iron ore, coking coal and thermal coal for export. In terminals with large and persistent stockpiles, the ever-changing geometry of stockpiles can impose challenging scheduling constraints. For those situations, we propose that each stockpile is modelled in detail, for instance as a collection of heterogeneous sized blocks. This is called a bench block model (BBM). We then demonstrate how stockpiles are manipulated via their BBM and how BBM can be integrated as a form of stockpile manager within a sophisticated DBET scheduling engine. Numerical testing of the DBET scheduling engine and three horizontal bench block model (HBBM) has been performed and indicates that the application of BBM is worthwhile, if not essential. The concept of BBM is generic, highly flexible, and integrable into existing optimisation routines. The results provided are superior to other approaches that model stockpiles as simple silos. We can provide schedules that are devoid of any stockpile geometry errors in contrast to others which cannot, and computational overheads to do this are no greater than previous approaches. In the three case studies considered, it was also pleasing to see that solutions of comparable quality with key performance criteria (KPI) equivalent to those constructed without any consideration of stockpile geometry are achievable. The new scheduling approach can significantly reduce the time to perform terminal planning and can increase the utilization of key resources within the terminal.